Building public–private partnerships for agricultural innovation in Latin America: Lessons from capacity strengthening - Hartwich, Frank; Gottret, Maria Veronica; Babu, Suresh Chandra; Tola, Jaime (International Food Policy Research Institute, 2007)
The International Service for National Agricultural Research¾on its own from 2002 until 2003, and as a division of the International Food Policy Research Institute thereafter has studied 124 public–private partnerships in agriculture in nine Latin American countries through its initiative on public–private partnerships for Agro-Industrial Research in Latin America...This paper examines...seven cases of public–private partnership building in which private- sector companies, producer associations, and research organizations engage in collaboration for the purpose of developing innovations in agricultural production and value chains. The paper considers different points of entry to partnership building, emulating best practices. The paper describes (a) how common interests among multiple stakeholders have been identified; (b) how partners have been motivated to participate in partnerships; (c) how the roles of different brokers within or outside the partnerships have fostered partnership development; and (d) how the contributions of partners have been negotiated to ensure that partnership arrangements are in alignment with the interests of the partners, their capacities, and the prevailing technological and market opportunities. The paper targets policymakers and administrators in agricultural development, and collaborators in research and innovation projects who are interested in issues of how best to build partnerships among public and private agents.